INCLUSIVE VOCATIONAL EDUCATION: EXPERIENCE, CHALLENGES AND OPPORTUNITIES OF EUROPEAN INTEGRATION (Innovative professional education, 2025)
Inclusive vocational education is a key element of social equality and ensuring access to education for all categories of education seekers, including persons with special educational needs (hereinafter referred to as PEN). The war in Ukraine has significantly affected the education system, including inclusive vocational education. Vocational (vocational) education institutions (hereinafter referred to as VTE) are forced to quickly adapt to new conditions, introducing distance and blended learning. Many students with special educational needs have lost the opportunity to attend school freely due to hostilities, destruction of infrastructure, forced displacement, or lack of access to necessary resources
Keywords: inclusion, vocational education, vocational (vocational and technical) education institution, integration